2012
DOI: 10.1007/s10456-012-9266-0
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol and its synthetic derivatives exert opposite effects on mesothelial cell-dependent angiogenesis via modulating secretion of VEGF and IL-8/CXCL8

Abstract: We examined the effect of resveratrol (RVT) and its two derivatives (3,3′,4,4′-tetrahydroxy- trans -stilbene and 3,3′,4,4′,5,5′-hexahydroxy- trans -stilbene) on human peritoneal mesothelial cell (HPMC)-dependent angiogenesis in vitro. To this end, angiogenic activity of endothelial cells (HUVEC, HMVEC, and HMEC-1) was monitored upon their exposure to conditioned medium (CM) from young and senescent HPMCs treated with stilbenes or to stilbenes themselves. Results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 55 publications
2
18
0
Order By: Relevance
“…Based on previous observations about a beneficial effect of resveratrol on anti-angiogenic responses in human peritoneal mesothelial cells (HPMCs), 12 and a hypothesis that trans-resveratrol could improve ultrafiltration via the anti-angiogenesis effect in PD-treated patients, here we tested the oral supplementation with trans-resveratrol in PD patients. To the best of our knowledge, this is the first report demonstrating the effects of trans-resveratrol on UF and neoangiogenesis in PD patients with ESRD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous observations about a beneficial effect of resveratrol on anti-angiogenic responses in human peritoneal mesothelial cells (HPMCs), 12 and a hypothesis that trans-resveratrol could improve ultrafiltration via the anti-angiogenesis effect in PD-treated patients, here we tested the oral supplementation with trans-resveratrol in PD patients. To the best of our knowledge, this is the first report demonstrating the effects of trans-resveratrol on UF and neoangiogenesis in PD patients with ESRD.…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol modulates HPMCs-dependent angiogenic responses in the opposite direction via modulating the secretion of VEGF and IL-8/ CXCL8. 12 Moreover, HPMCs play an important role in peritoneal angiogenesis and fibrosis. In clinical studies, resveratrol is used orally among normal people, obese participants, and diabetes patients.…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms have been unraveled, for example, downregulation and/or inhibition of VEGF, HIF-1 α , Flk-1, and Src [68, 69]. Various signaling pathways contribute to inhibition of angiogenesis such as the eukaryotic elongation factor-2 kinase-regulated pathway, the GSK3 β / β -catenin/TCF-dependent pathway, NF- κ B-related signaling, and cytokine signaling (IL8/CXCL8) [43, 44, 70, 71]. The antiangiogenic activity of verbascoside and eriodictyol tetraacetate has not been described yet.…”
Section: Discussionmentioning
confidence: 99%
“…We have established a protocol for primary BAEC culture and previously performed fundamental investigations on their morphology and functions [20, 26]. Additionally, Mikula-Pietrasik et al recently demonstrated that the resveratrol and its derivatives have cell-specific effects, which were confirmed by having different effects on the proliferation of human from different sources [15]. Thus, we selected BAECs as our model for in vitro studies as a prelude to in vivo studies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of a wide range of concentrations of resveratrol administered to a uniform population of ECs are lacking. Such studies are required to comprehend the diverse and sometimes contradictory cellular effects of resveratrol [15]. Previous studies demonstrated that resveratrol has biphasic properties in relation to its concentration on EC proliferation, with no effects at low concentrations (0.1–25  μ M) and induced apoptosis at high doses (such as 100  μ M) in human umbilical vein endothelial cells (HUVECs) [16].…”
Section: Introductionmentioning
confidence: 99%